PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP PEMAHAMAN KONSEP FISIKA SISWA - ANDRIONO MANALU (LP2MTBM MAKARIOZ, 2022)
This study aims to determine the effect of the problem based learning model on students' understanding of physics concepts in the kinematics of motion material in class X SMA Negeri 2 Pematangsiantar T.A 2021/2022. This type of research is a preexperimental design study with a research population of all class X PMIA SMA Negeri 2 Pematangsiantar T.A 2021/2022. With the Cluster Random Sampling technique, the research sample was obtained for class X PMIA 2. The instrument used was a concept understanding test in the form of an essay test which had been validated by 2 validators and LKPD. After the treatment was carried out on the students, the posttest average score was 70.14 and the overall N-gain score for students was 0.67. The results showed that the students' understanding of physics concepts taught by the problem based learning model increased from 27.06 to 70.14. So that there is an influence of problem based learning learning models assisted by practicum on motion kinematics material on understanding physics concepts for class X students of SMA Negeri 2 Pematangsiantar T.A 2021/2022. During class learning students get a final grade with a good assessment category